Comparison of Dentoskeletal Changes In Skeletal Class II Malocclusion Using two Different Fixed Functional Appliances: A 2 Case Report - Dadhwal, Sahira; Isha Aggarwal; Sanjay Mittal; Merry; Abida Parveen (UNIVERSITY JOURNAL OF DENTAL SCIENCES, 2023)
Introduction: Class II malocclusion refers to an anteroposterior discrepancy that could be characterized by a dentoalveolar and/or skeletal involvement. When skeletal involvement is present, mandibular retrusion is the primary etiological factor. Several methods have been proposed for treatment of this malocclusion and their choice would depend on the degree of dentoalveolar or skeletal involvement, patient growth pattern, age, cooperation and main complaint. Fixed functional appliances are an excellent option in patients with growth potential. These appliances have the advantage of not depending on patient compliance, which may be related to more predictability. Aim: This article presents 2 case reports that compare the dentoskeletal changes of patients diagnosed with skeletal class II treated with Forsus fatigue resistant device (FFRD) and Powerscope class II corrector (PS). Conclusion: Power Scope Class II corrector and Forsus fatigue resistant device (FFRD) are promising appliances that is relatively simple to install and easy to maintain by patients this directly helps the orthodontist in maintaining patient compliance to achieve the predicted treatment outcome.